3. Manajemen Kualitas Air Media Budidaya Ikan Lele Sangkuriang (Clarias gariepinus) dengan Teknik Probiotik pada Kolam Terpal di Desa Vokasi Reksosari, Kecamatan Suruh, Kabupaten Semarang - Diana Rachmawati; Istiyanto Samidjan; Heryoso Setyono (Fakultas Perikanan Universitas Pekalongan, 2016)
Cultivation of Sangkuriang catfish (Clarias gariepinus) intensively can result in the decrease of quality of cultivation media water, among others the decrease of dissolved oxygen content and the increase of waste content especially organic nitrogen. The technology has been implemented to manage the activities of Sangkuriang catfish cultivation in Reksosari Vocational Sub-District, Suruh District, Semarang Regency using probiotic in cultivation media. This study aimed to compare the growth of Sangkuriang catfish raised by using probiotic and non-probiotic system cultivation media. The test animals used in this study were Sangkuriang catfish seedlings of 10 days for 500 seedlings raised for 30 days. The observation was conducted on day-0, day-15, and day-30. The observed parameters of growth were water temperature, dissolved oxygen, pH, and ammonia. The study result indicated that there was a difference in length and weight increase of Sangkuriang catfish in probiotic and non-probiotic application cultivation media. Although the increase of growth was not significant, but it could give illustration that Sangkuriang catfish raised using probiotic application experienced a better growth. It indicated that the feed given and the raising media could support the growth of Sangkuriang catfish. The raising media implementing probiotic technique showed a better and relatively ideal condition for Sangkuriang catfish. Keyword: Sangkuriang, catfish, management, water quality, probiotics